The main predictors of well-being and productivity from a gender perspective - Martínez-Martínez, Kevin; Llorens, Susana; Cruz-Ortiz, Valeria; Reyes-Luján, Juanjo; Salanova, Marisa (Frontiers in Psychology, 2024)
Introduction Gender difference management is one of the most challenging dimensions organizations must cope with to adapt to VUCA (Volatile, Uncertain, Complex and Ambiguous) environments. The aim of this study is to identify the main drivers (i.e., most influential job resources, job demands, and organizational practices) of healthy employees and organizational outcomes assessing the differences between men and women, based on the HERO (HEalthy and Resilient Organization) Model. Methods Data were collected through the HERO-CHECK Questionnaire: job demands (e.g., quantitative overload), job (e.g., team coordination) and personal resources (e.g., emotional competence), healthy organizational practices (e.g., work-family balance practices), healthy employees (e.g., work engagement) and healthy organizational outcomes (e.g., in-role performance). The sample consisted of 2,128 professionals (70% female) from 8 organizations. Gender-based multigroup SEM was performed using R 4.1.2. Results Results of the multigroup SEM analysis show a good fit of the HERO model and support the existence of configural invariance among gender groups. This research shows that women perceive more resources to cope with demands, in consequence, they perceive more well-being and better job performance. Regardless of gender, coordination, horizontal trust, vertical trust, and emotional competence stand as relevant resources for achieving healthy employees and healthy organizational outcomes. However, there are gender-specific predictors of healthy employees and healthy organizational outcomes, depending on gender. Discussion Based on these results, gender-related recommendations for promoting specific resources (e.g., autonomy in women) and preventing specific demands (e.g., mobbing in men) may be suggested in organizational contexts.